Microstructure and mechanical properties of WC-Co reinforced with NbC - Wilson Acchar; Cordt Zollfrank; Peter Greil (Materials Research, 2004)
Cemented carbides such as tungsten carbide-cobalt WC-Co composites have been widely used as cutting tool materials. Several reports have shown the influence of different factors such as grain size, type and amount of binder phase and the addition of hard particles on the properties of WC-Co. The purpose of this work was to investigate the effect of niobium carbide on the microstructure and mechanical properties of WC-Co. Specimens of WC-Co reinforced with NbC were mixed and subsequently hot-pressed in a inert atmosphere. The WC-Co-NbC composite material exhibited high hardness values (18.9 GPa), flexural strength (2100 MPa) and fracture toughness (11.2 MPa.m½ ). TEM analysis has shown a bimodal grain size distribution of WC.